121-6x=12x+23

Simple and best practice solution for 121-6x=12x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 121-6x=12x+23 equation:


Simplifying
121 + -6x = 12x + 23

Reorder the terms:
121 + -6x = 23 + 12x

Solving
121 + -6x = 23 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
121 + -6x + -12x = 23 + 12x + -12x

Combine like terms: -6x + -12x = -18x
121 + -18x = 23 + 12x + -12x

Combine like terms: 12x + -12x = 0
121 + -18x = 23 + 0
121 + -18x = 23

Add '-121' to each side of the equation.
121 + -121 + -18x = 23 + -121

Combine like terms: 121 + -121 = 0
0 + -18x = 23 + -121
-18x = 23 + -121

Combine like terms: 23 + -121 = -98
-18x = -98

Divide each side by '-18'.
x = 5.444444444

Simplifying
x = 5.444444444

See similar equations:

| 5x+3=7x+-3 | | -6(6y+4)-(-5y-7)=1 | | 3(n+6)=-9 | | 4(7x-1)=3(2x-1)-4(x+6) | | (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 | | 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 | | 0=4(-4x^2+10x-6) | | 3(x+14)=69 | | z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 | | 9=3x-7 | | -120x+3000=-160x+4000 | | 7+2x=5x-5 | | 4x+2=32 | | 67-3x=9x+16 | | 7/9y+2+5/9y+6 |

Equations solver categories